Behind the Curtain, Impact Benefit Agreement Transparency in Nunavut - Hummel, Chris (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2019)
Impact Benefit Agreements are typically hidden from public view by confidentiality clauses. However, a recent trend towards public disclosure of IBAs in Nunavut has made scrutiny possible. In light of this unique disclosure, this paper analyses the contents of Nunavut’s IBAs and the short-term consequences of their transparency, reaching three conclusions : (1) the contents of Nunavut’s IBAs are quasi-legislative, resembling public law more than private law in scope and scale — a characterization which warrants transparency ; (2) IBAs’ increasing role in the Duty to Consult may further warrant transparency, and (3) IBA transparency in Nunavut has allowed ideas to spread among Nunavut’s communities and has invited constructive public and academic scrutiny. In reaching these conclusions, this paper does not suggest that all IBAs ought to be publicized. There are a variety of reasons why both Indigenous communities and extractive proponents opt for IBA confidentiality. Nonetheless, the trend away from confidentiality in Nunavut invites a broader discussion about the merits of IBA transparency.